2002
DOI: 10.1006/jmsc.2001.1126
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic classification of marine habitats in coastal Newfoundland

Abstract: A digital acoustic seabed classification system, QTC View (Series IV) was used in the coastal waters of Newfoundland to characterize and classify marine benthic habitats. The QTC View system was calibrated in Placentia Bay at sites identified independently during a submersible research program. Four different habitats were used for calibration of the QTC View system: mud, gravel, rock, and macroalgae on rock. These different habitats were used as a ''training'' catalogue for real-time classification of marine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…More recently acoustic ground-discrimination systems (AGDS) have been developed to detect the acoustic-reflectance properties of the seabed. Indeed, the nature of bottom echoes is influenced not only by basic sediment grainsize parameters, sediment sorting, microtopography, sediment density and porosity, but also by the presence, concentration and type of benthic fauna and flora (TSEMAHMAN & COLLINS, 1997;COLLINS & GALLOWAY, 1998;BORNHOLD et al, 1999;HAMILTON et al, 1999;KLOSER et al, 2001;ANDERSON et al, 2002;HUTIN et al, 2005). RoxAnnì (CHIVERS et al, 1990) and QTC VIEWì (COLLINS et al, 1996) are two widely used AGDSs to extract shape, energy or both features contained in the bottom acoustic signals.…”
Section: Single-beam Echo-sounders (Sbes)mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently acoustic ground-discrimination systems (AGDS) have been developed to detect the acoustic-reflectance properties of the seabed. Indeed, the nature of bottom echoes is influenced not only by basic sediment grainsize parameters, sediment sorting, microtopography, sediment density and porosity, but also by the presence, concentration and type of benthic fauna and flora (TSEMAHMAN & COLLINS, 1997;COLLINS & GALLOWAY, 1998;BORNHOLD et al, 1999;HAMILTON et al, 1999;KLOSER et al, 2001;ANDERSON et al, 2002;HUTIN et al, 2005). RoxAnnì (CHIVERS et al, 1990) and QTC VIEWì (COLLINS et al, 1996) are two widely used AGDSs to extract shape, energy or both features contained in the bottom acoustic signals.…”
Section: Single-beam Echo-sounders (Sbes)mentioning
confidence: 99%
“…The shape of the return wave signal reflects a number of seabed characteristics such as sediment composition, seabed roughness and biological components, which can be used to classify and map seabed types (WIENBERG and BARTHOLOMÄ, 2005). Several studies using the single-beam acoustic seabed classification system QTC VIEW TM Series IV have revealed its ability to distinguish various bottom types and associate them with distinct acoustic properties (HAMILTON et al, 1999;PRESTON, 2001;ANDERSON et al, 2002;FREITAS et al, 2005& FREITAS et al, 2006. These studies showed that the acoustic response may depend on the surface roughness, sediment grain size, the presence/absence of shell debris and some infaunal species, texture properties of the sediment and sediment porosity, while being independent of depth.…”
Section: Single-beam Echo-sounders (Sbes)mentioning
confidence: 99%
“…This is now done with high-resolution bathymetry data and seabed classification which identifies different habitats across a continuum of spatial scales (ANDERSON et al, 2002). Seabed classification employing acoustics is a recent science, largely driven by the development of commercial systems for the classification of superficial sediments and habitats of demersal species (ANDERSON et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Various methods based on different acoustic measurements have been developed for the purpose of describing seabed properties (ORLOWSKI, 1989;COLLINS et al, 1996;ANDERSON et al, 2002;ELLINGSEN et al, 2002;FREITAS et al, 2005FREITAS et al, , 2006TĘGOWSKI, 2005;WIENBERG;BARTHOLOMA, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For visualization of coral reefs, however, useful images are limited to those environments in shallow, clear water less than 10-20 m depth (FINKBEINER, STEVEN-SON, and SEAMAN, 2001;FINKL, 2005;HOPLEY, 1996;PURK-IS, 2005). Other remote sensing tools must be implemented to map turbid and deep reefs (ANDERSON, GREGORY, and COLLINS, 2002;FINKL, BENEDET, and ANDREWS, 2005;GAL-LOWAY, 2001). Among these devices are high-resolution bathymetry and acoustic ground discrimination (HAMILTON, MULHEARN, and POECKERT, 1999;.…”
Section: Introductionmentioning
confidence: 99%